Permanence and Extinction for a Nonautonomous Malaria Transmission Model with Distributed Time Delay - Xiaohong Zhang; Jianwen Jia; Xinyu Song (Journal of Applied Mathematics)
We study the permanence, extinction, and global asymptotic stability for a nonautonomous malaria transmission model with distributed time delay. We establish some sufficient conditions on the permanence and extinction of the disease by using inequality analytical techniques. By a Lyapunov functional method, we also obtain some sufficient conditions for global asymptotic stability of this model. A numerical analysis is given to explain the analytical findings.